Approaches of teaching statistics in high school programs of study - Gómez Blancarte, Ana Luisa; Chávez Aguilar, Rosa Daniela; Miranda Viramontes, Isaias (IE Revista de Investigación Educativa de la REDIECH, 2022)
With the idea of exploring the current condition of teaching statistics in Mexican higher secondary education (HSE), the objective of this article is to identify the approach of teaching statistics promoted by syllabuses of this discipline in HSE. Based on the theoretical ideas of the statistical literacy, reasoning and thinking approaches, a set of indicators were constructed to analyze, following a documentary research technique, eight statistics syllabuses of the main HSE subsystems in the country. The results show that, although the syllabuses show elements of the three approaches, most of these programs seem to promote teaching aimed at the development of elements of a statistical literacy. The importance of some conditions of statistics teaching in HSE are highlighted and a teaching that promotes elements of statistical reasoning and thinking is discussed.